How does economic development in eastern Europe affect Austria's regions? A multiregional general equilibrium framework - Johannes Bröcker; Martin Schneider (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 1999)
This paper presents a framework for analysing the effects of economic development in Eastern Europe on Austria's regions. Therefore we concentrate on the effects of enhanced East-West trade, which results from the economic development in the transition countries. The analytical framework we use is a multiregional computable general equilibrium model for the Austrian economy. The model is based on an Arrow-Debreu-equilibrium. It contains the 9 Austrian Federal Provinces (NUTS-II) which are linked by trade flows with 4 of the Central and Eastern European countries and with the rest of the world. The simulation results of one trade scenario show how structural and welfare effects differ for the Austrian regions.
Keywords: C68; F14; F15; F17; R13; 330; Regionaler Außenhandel; Außenhandelseffekt; Allgemeines Gleichgewicht; Regionale Entwicklung; Österreich